Impact of antibiotic choice on immune response and antibiotic resistance development in piglets experimentally infected with Escherichia coli - Cantas, Leon; Fenton, Christopher G.; Bato, Emese; Paulssen, Ruth H.; Sørum, Henning (Frontiers in Cellular and Infection Microbiology, 2025)
The rapid mobility of antibiotic resistance genes (ARGs) represents a growing global One Health concern. However, further in vivo studies are needed to better understand ARG dissemination in actual clinical settings. To this end, a piglet model of enteric colibacillosis with the causative bacterium carrying an R-plasmid, was used to track the expression of genes involved in the bacterial SOS response, plasmid transfer, and porcine immune responses under both effective and ineffective antibiotic treatments. Analysis of gut samples showed a significant reduction (p < 0.05) in the expression of R-plasmid transfer genes in groups receiving effective enrofloxacin, with or without probiotics or meloxicam. Conversely, ineffective tetracycline and sub-inhibitory enrofloxacin resulted in a significant increase (p < 0.05) in the expression of bacterial SOS response and R-plasmid transfer genes. Inflammatory gene expression was upregulated in the groups receiving ineffective antimicrobial treatment, whereas anti-inflammatory cytokines exhibited the opposite trend in effectively treated piglets. These findings highlight the importance of selecting the correct antibiotic and administering it at an effective dosage. The improper use of antibiotics or their administration at subinhibitory concentrations can result in high mortality/morbidity rates and accelerate the spread of ARGs.